Voluntary Running and Estrous Cycle Modulate ΔFOSB in the Suprachiasmatic Nucleus of the Wistar Rat - Ayano Shiba; Marene H. Hardonk; Ewout Foppen; Tess Kool; Susanne E. la Fleur; Paul J. Lucassen; Chun-Xia Yi; Dirk Jan Stenvers; Joram D. Mul; Andries Kalsbeek (Journal of Circadian Rhythms)
The hypothalamic suprachiasmatic nucleus (SCN), the circadian pacemaker of the mammalian brain, integrates both environmental and endogenous information to modulate various physiological and behavioral processes. Both light and physical activity entrain SCN circadian rhythmicity, but the underlying molecular mechanisms for physical activity remain elusive. Repetitive neuronal stimulation results in accumulation of the stable transcription factor ΔFOSB, that has been implicated in long-term brain plasticity, altered neuronal excitability, and changes in behavior. In rodents, voluntary wheel running (VWR) mimics aspects of exercise training and increases ΔFOSB in several brain regions. Whether VWR also alters ΔFOSB in the SCN is unexplored. Here, young-adult male and female Wistar rats were housed sedentary or allowed to run for four weeks followed by quantification of ΔFOSB in the SCN. VWR lowered SCN ΔFOSB-positive cell numbers in males and females compared to sedentary housing. Total running distance did not correlate with ΔFOSB suppression. Analysis taking estrous cycle into account revealed that ΔFOSB-positive cell numbers were cyclic in sedentary females, being lowest during proestrus and highest during diestrus. Remarkably, this cyclicity was absent in runners, where ΔFOSB-positive cell numbers remained comparable to those observed during proestrus in sedentary controls. Finally, estradiol replacement following ovariectomy in sedentary females lowered SCN ΔFOSB-positive cell numbers. Thus, VWR and estrous cycle, via, at least in part, estradiol, modulate SCN ΔFOSB. Given its role in long-term plasticity and behavioral adaptations, ΔFOSB may provide a molecular link between VWR and/or estrous cycle and the output of the SCN and its related behavioral adaptations.